Seroprevalence of Hepatitis B Virus Infection Among Pregnant Women Attending Dei – dei General Hospital Abuja, Nigeria. - Yusuf, Lamidi; Okolo, Oseni M.; Joseph, Caleb A.; Yusuf, Abdulwasii Olanrewaju (British Journal of Healthcare and Medical Research, 2022)
The study was carried out to investigate seroprevalence of Hepatitis B virus (HBV) infection among pregnant women attending Dei-Dei general hospital in Bwari Area Council, Abuja. The research work was a hospital based cross-sectional study that involved 200 pregnant women of which only 116 were consented, after ethical clearance (approval) was obtained from the Hospital Management. Demographic variables and information considered as risk factors were obtained by administering questionnaires to the participants. Plasmas obtained were stored at – 20oC±2 until screened for Hepatitis B surface antigen. Hepatitis B surface antigen (HBsAg) in the plasma was detected using SWE–CARE Hepatitis B test strip. The strip is a rapid chromatographic immunoassay for the qualitative detection of Hepatitis B surface Antigen (HBsAg) in whole blood or serums or plasma. The result obtained is statically analyzed using Chi-square test to establish association between the risk factors and HBsAg seropositivity at significant level of p < 0.05. Statistically, education, marital status, alcoholism and sex partners were statistically significance among the demographic variables in this study. The HBV seroprevalence rate of 4.3% in this study implies that Dei – Dei, FCT Abuja, Nigeria is an intermediate endemic area of HBV infection based on the criteria of World Health Organization. The demographic variables sampled were major contributing factors to the results obtained.